2022
DOI: 10.3390/polym14071320
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of PBSA Films by Elite Aspergillus Isolates and Farmland Soil

Abstract: Plastic films are widely used in current agricultural practices; however, most mulch films used are discarded and buried in the land after harvest, having adverse environmental impacts. To solve this environmental problem, the demand for biodegradable mulch has been increasing in recent years. Polybutylene succinate-co-adipate (PBSA) is a biodegradable polymer with good ductility and can be used for packaging and mulching. In this study, we isolated two elite fungal strains for PBSA degradation from farmlands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 63 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…It was found that Fe 2+ and Ca 2+ enhanced the function, whereas Cu 2+ and Hg 2+ inhibited it. Chien et al ( 2022 ) selected two elite PBSA-degrading Aspergillus strains, namely, A. terreus HC and A. fumigatus L30, from soil samples in Taiwan and incubated in carbon-free basal medium. Results showed that A. fumigatus and A. terreus deteriorated PBSA films by about 26% and 42% respectively within 1 month.…”
Section: Fungi: a Major Recycler In The Environmentmentioning
confidence: 99%
“…It was found that Fe 2+ and Ca 2+ enhanced the function, whereas Cu 2+ and Hg 2+ inhibited it. Chien et al ( 2022 ) selected two elite PBSA-degrading Aspergillus strains, namely, A. terreus HC and A. fumigatus L30, from soil samples in Taiwan and incubated in carbon-free basal medium. Results showed that A. fumigatus and A. terreus deteriorated PBSA films by about 26% and 42% respectively within 1 month.…”
Section: Fungi: a Major Recycler In The Environmentmentioning
confidence: 99%
“…Johnson et al investigated how the microorganism growing on plastic material may either utilize the plasticizer molecule of starch cellulose or the other polymer [ 90 ]. Fungi are able to degrade a wide variety of polymers through the production of several enzymes such as cellulase and amylase [ 91 , 92 , 93 ]. The active enzymes have been grouped as esterases, lipases, proteases, and ureases which degrade the polyurethane substrate by cleaving the ester bonds [ 94 ].…”
Section: Biodegradationmentioning
confidence: 99%
“…However, the biosynthesis of these monomers from sugars allowed us to obtain fully bio-based PBSA [ 18 , 19 ]. Bio-derived PBSA has now found application in various industrial sectors (packaging and textile) with recent emerging trends in the agriculture field where PBSA is particularly employed in mulching films, bags, and plant pots [ 20 , 21 ], and in the automotive sectors as a composite material for internal building parts [ 22 ]. PBSA has good mechanical and thermal properties combined with excellent processability through conventional techniques such as extrusion, injection molding, and thermoforming [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Zhao et al [ 30 ] reported the isolation of a fungus from compost, Aspergillus versicolor , that can induce the hydrolytic degradation of PBSA. Chien et al [ 21 ] selected two elite Aspergillus strains to aid PBSA degradability in soil at moderate temperatures. In addition, Nishioka et al [ 31 ] found that bacteria widely present in the soil and compost cause hydrolytic cleavage of ester linkages.…”
Section: Introductionmentioning
confidence: 99%